2022
DOI: 10.1111/ddi.13486
|View full text |Cite
|
Sign up to set email alerts
|

Fish zeta diversity responses to human pressures and cumulative effects across a freshwater basin

Abstract: Aim Declining biodiversity across ecosystems and myriad human pressures necessitate high‐level regional assessments for effective management. Evaluation of biodiversity patterns and stressor accumulation through beta diversity and cumulative effect analyses are two key methods for management prioritization. This study links these concepts to develop a novel cumulative effect metric based on beta diversity responses. Location Fraser River basin, British Columbia, Canada. Methods Multi‐Site Generalized Dissimila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 69 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Landscape level studies have assessed the dependence of measured shifts in fish communities upon current and past land use changes, with some evidence of generalization in thresholds for urbanization and agriculture effects on compositional and richness changes (Chen and Olden, 2020). While land use variables provide the first evidence that urbanization and agriculture change fish communities, pinpointing the specific variables associated with these land uses can give additional insight into what environmental monitors should be measured when completing bioassessments (Waite et al, 2021;Iacarella, 2022). For example, Stoczynski et al (2021) found that dam density affected how species replaced one another across the landscape, Ortega et al (2021) identified impervious surfaces as a proxy for urbanization, and Waite et al (2021) highlighted how contaminants in water and sediment were just one of multiple urbanization and agricultural stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Landscape level studies have assessed the dependence of measured shifts in fish communities upon current and past land use changes, with some evidence of generalization in thresholds for urbanization and agriculture effects on compositional and richness changes (Chen and Olden, 2020). While land use variables provide the first evidence that urbanization and agriculture change fish communities, pinpointing the specific variables associated with these land uses can give additional insight into what environmental monitors should be measured when completing bioassessments (Waite et al, 2021;Iacarella, 2022). For example, Stoczynski et al (2021) found that dam density affected how species replaced one another across the landscape, Ortega et al (2021) identified impervious surfaces as a proxy for urbanization, and Waite et al (2021) highlighted how contaminants in water and sediment were just one of multiple urbanization and agricultural stressors.…”
Section: Introductionmentioning
confidence: 99%